Construction of enterprise data asset operation platform - Xiaozheng DU; Xiaofei WANG; Na LI; Lei LOU; Xin LIN (大数据)
It has become a social consensus that data is the core strategic asset for enterprises.In the wave of digital transformation, businesses drive digitization through data resource utilization and commercialization to fully unleash data asset value.This paper examines how to establish a practical management system by effective data asset operations from the supply side, so as to enhance data quality and security.It also explores how to connect internal and external data by data asset operations from the demand side, so as to foster deep integration with business and enriching data asset application scenarios.The data asset operation platform supports the operational loop of data assets, enabling online, standardized, and configurable processes, meeting the needs for automated and intelligent operations.